2017
DOI: 10.1177/0950422217693963
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship in vocational education

Abstract: Vocational entrepreneurship education is associated with specific techniques and teaching methods, including face-to-face student contact and knowledge alignment with labour market needs. The authors argue that entrepreneurship education provides particular benefits in different educational conditions and modes because it allows students to develop entrepreneurial behaviour for different vocations. This article presents the results of a study involving students enrolled on technical courses at a publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The objective conditions for relevant research are similar to Suartini's study, which also examines the need for innovation in vocational education concerning teaching and governance. Unlike Acharya and Smit's study, which explains the relationship between vocational education and skill development in fostering entrepreneurship (Shrivastava & Acharya, 2021;Stadler & Smith, 2017). Research conducted by previous study found that the benchmarking technique had a significant positive effect on managerial governance and organizational performance (Bogetoft, 2013;Gunasekaran, 2021).…”
Section: Introductionmentioning
confidence: 82%
“…The objective conditions for relevant research are similar to Suartini's study, which also examines the need for innovation in vocational education concerning teaching and governance. Unlike Acharya and Smit's study, which explains the relationship between vocational education and skill development in fostering entrepreneurship (Shrivastava & Acharya, 2021;Stadler & Smith, 2017). Research conducted by previous study found that the benchmarking technique had a significant positive effect on managerial governance and organizational performance (Bogetoft, 2013;Gunasekaran, 2021).…”
Section: Introductionmentioning
confidence: 82%
“…In complex with the personality open culture, and deep professional specialization, we are able to envisage the future ideal of man, agreeing with Kreber (2015), especially in the contexts of adaptation to high social dynamics, keeping up the mobility and possibility of conscientious choice of activity as a calling (Bernardi & Triventi, 2018). In this aspect we agree with those, who follow Stadler & Smith (2017), and argue the forming of entrepreneurship within the professional education, bringing out another significant condition of successful individual adaptation to the world of high social dynamics.…”
mentioning
confidence: 77%
“…EE in vocational education was originally targeted at students in economics and management (Hidayat, 2017;Stadler & Smith, 2017). However, it has expanded to other fields such as engineering, health, and tourism.…”
Section: Entrepreneurial Educationmentioning
confidence: 99%